Mating pattern and pollen dispersal in an advanced generation seed orchard of Cunninghamia lanceolata (Lamb.) Hook - Wu, Hanbin; Zhao, Shirong; Wang, Xihan; Duan, Aiguo; Zhang, Jianguo (Frontiers in Plant Science, 2022)
Seed orchards represent the link between forest breeding and conifer production forests, and their mating patterns determine the genetic quality of seed orchard crops to a large extent. We genotyped the parental clones and their open pollination offspring in the third-generation seed orchard of Chinese fir using microsatellite markers and observed the synchronization of florescence in the seed orchard to understand the genetic diversity and mating structure of the seed orchard population. Genetic coancestry among parental clones was detected in the third generation seed orchard of Chinese fir, and the genetic diversity of the open-pollinated offspring was slightly higher than that of the parental clones. The external pollen contamination rate ranged from 10.1% to 33.7%, 80% of the offspring were produced by 44% of the parental clones in the orchard, and no evidence of selfing was found. We found that 68.1% of the effective pollination occurred within 50 m, and 19.9% of the effective pollination occurred in the nearest neighbors. We also found that successful mating requires about 30% of florescence overlap between males and females, and there was a significant positive correlation between male reproductive energy and male parental contribution. Our results provide a valuable reference for the management and design of advanced generation seed orchards.